2007
DOI: 10.1182/blood-2006-12-063503
|View full text |Cite
|
Sign up to set email alerts
|

EPO modulation of cell-cycle regulatory genes, and cell division, in primary bone marrow erythroblasts

Abstract: Erythropoietin (EPO's) actions on erythroblasts are ascribed largely to survival effects. Certain studies, however, point to EPO-regulated proliferation. To investigate this problem in a primary system, Kit pos CD71 high erythroblasts were prepared from murine bone marrow, and were first used in the array-based discovery of EPO-modulated cell-cycle regulators. Five cell-cycle progression factors were rapidly up-modulated: nuclear protein 1 (Nupr1), G1 to S phase transition 1 (Gspt1), early growth response 1 (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 82 publications
(114 reference statements)
2
77
0
Order By: Relevance
“…We previously showed that unscheduled CycG2 expression inhibits DNA synthesis, blunts CDK2 (but not CDK4) activity (13), and induces a p53-dependent G 1 -phase cell cycle arrest (15). Similar results have since been replicated by others using various epitope-tagged forms of CycG2 in several cell lines (10,13,14,16,24). Here we show that the potent cell cycle arrest response of HCT116 cells to exogenous CycG2 requires intact alleles for Chk2 and p53 (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We previously showed that unscheduled CycG2 expression inhibits DNA synthesis, blunts CDK2 (but not CDK4) activity (13), and induces a p53-dependent G 1 -phase cell cycle arrest (15). Similar results have since been replicated by others using various epitope-tagged forms of CycG2 in several cell lines (10,13,14,16,24). Here we show that the potent cell cycle arrest response of HCT116 cells to exogenous CycG2 requires intact alleles for Chk2 and p53 (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…We showed that overexpression of CycG2 inhibits CDK2 activity and that the CycG2-mediated G 1 /S-phase cell cycle arrest is p53-dependent (13,15). Subsequent studies determined that even moderate up-regulation of ectopic CycG2 expression inhibits cellular proliferation (10,16,24). We found that exogenous and endogenously expressed CycG2 is a CRM1-dependent nucleocytoplasmic shuttling protein that localizes to the cytoplasmic-cytoskeletal compartment of replicating cells where it associates with centrosomes via AKAP450 (15).…”
mentioning
confidence: 90%
“…microcirculation disturbances and systemic disorders. However, effective prevention and control measures for HAPC have yet to be utilized (15,16). In addition, it has been reported that GML is the most frequent concomitant disease to HAPC.…”
Section: Discussionmentioning
confidence: 99%
“…24 In turn, the phosphorylated form of JAK2 activates STAT5, 25 which modifies the expression of genes involved in proliferation, differentiation, and survival of erythroid precursors. 26,27 Erythropoiesis requires the coordinated biosynthesis of heme and globin chains to produce Hb during the differentiation process. Proteins that control iron intake and heme biosynthesis are reviewed in "Coordination of erythroid iron homeostasis, heme metabolism, and globin synthesis.…”
Section: Ineffective Erythropoiesis Important Players Involved In Erymentioning
confidence: 99%